Anisotropic response measurements of ZnWO4 scintillators to neutrons for developing a direction-sensitive dark matter detector. (22nd February 2020) - Pedersen, Juan W; Sekiya, Hiroyuki; Ichimura, Koichi
Abstract: The scintillation yields of ZnWO$_4$ crystals change depending on the incident direction of particles. This property can be used as a direction-sensitive dark matter detector, so we investigated the ZnWO$_4$ light yields ratio of neutron-induced nuclear recoils to gamma-ray-induced electron recoils (quenching factor). Two surfaces almost perpendicular to the crystal axis of ZnWO$_4$ were irradiated with a quasi-monochromatic neutron beam of 0.885 MeV, and the quenching factors of both surfaces for the oxygen-nucleus recoil in the ZnWO$_4$ crystal were measured. The obtained quenching factors of the two surfaces were $0.235 ± 0.026$ and $0.199 ± 0.020$, respectively, confirming 15.3% anisotropy.